An empirical investigation of strategic management accounting in hotels. Issue 5 (13th July 2015) - Pavlatos, Odysseas
Abstract : Purpose: – The purpose of this paper is to investigate the relationship between contextual factors, strategic management accounting (SMA) and historical performance in hotels. Design/methodology/approach: – An empirical survey was conducted on a sample of 106 leading hotels in Greece. Findings: – The analysis of the survey data indicates that seven contingent factors affect SMA usage in hotels: The seven factors are perceived environmental uncertainty, structure, quality of information system (IS) information, organizational life cycle stage, historical performance, strategy and size. The findings also indicate that lagging performance affects SMA and that this effect is moderated by the perceived environmental uncertainty. Research limitations/implications: – Some of the limitations are inherent to the survey method used, such as the use of perceptual measures and the potential of common method bias. Data were collected from the Greek hospitality industry, and consequently, the results may be generalizable only to that population. Practical implications: – The accounting professionals and hotel managers will also be benefited, as the study aims to identify the most relevant SMA tools adopted in the hotel industry, as well as the relationship between these tools and other external and organizational factors. Originality/value: – This research adds to the current knowledge in management accounting system design in hotels. This paper increases the understanding as to why hotels are more likely to implement SMA. The results provide the first empirical evidence of the relation between SMA usage, organizational factors, external factors and historical performance in hotels.